2017
DOI: 10.3892/mmr.2017.7326
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of N-acetylcysteine in reducing monocrotaline-induced pulmonary hypertension in rats: Inhibiting the expression of Nox1 in pulmonary vascular smooth muscle cells

Abstract: The aim of the present study was to investigate the impact of N‑acetylcysteine (NAC) on the expression of reduced nicotinamide adenine dinucleotide phosphate oxidase 1 (Nox1), and the proliferation and apoptosis of pulmonary artery smooth muscle cells (PASMCs) in rats exhibiting monocrotaline (MCT)‑induced pulmonary hypertension, and to investigate the possible mechanisms and treatment roles of NAC in pulmonary vascular remodeling (PVR). A total of 18 Wistar rats were randomly divided into three groups: The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…NOX1 activity promoted Grem1 upregulation by activating the transcription factor CREB. It has been previously shown that CREB is selectively activated by hypoxia in the mouse lung in vivo and is also activated in the Sugen-hypoxia model of PAH in rats [ 69 , 70 , 115 ].…”
Section: The X Chromosome In Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX1 activity promoted Grem1 upregulation by activating the transcription factor CREB. It has been previously shown that CREB is selectively activated by hypoxia in the mouse lung in vivo and is also activated in the Sugen-hypoxia model of PAH in rats [ 69 , 70 , 115 ].…”
Section: The X Chromosome In Pulmonary Hypertensionmentioning
confidence: 99%
“…When NOX1 expression and activity in monocrotaline-induced pulmonary hypertension in rats was inhibited, pulmonary vascular resistance was reduced and pulmonary hypertension attenuated [ 69 ]. Furthermore, hypoxia-induced pulmonary hypertension was attenuated in female NOX1 −/− deficient mice [ 72 ].…”
Section: The X Chromosome In Pulmonary Hypertensionmentioning
confidence: 99%
“…NOX1 expression is greater in PAs from PAH patients compared to vessels from control patients [ 83 ] and contributes to the proliferation of both PAEC [ 83 ] and PASMC [ 86 ]. In monocrotaline-induced PAH model, NOX1 expression is increased in PASMCs [ 87 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…In monocrotaline-induced PAH model, NOX1 expression is increased in PASMCs [ 87 ]. Moreover, N-acetylcysteine, which suppresses NOX1 expression, is protective against monocrotaline-induced PAH [ 86 ]. In addition to PAH, NOX1 has also been shown to participate in PH elicited by CH as evidence by effects of genetic global deletion of NOX1 to abolish the CH-induced elevation in right ventricular systolic pressure (RVSP), right ventricle (RV) hypertrophy and PA remodeling in mice [ 98 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…Nevertheless, the pathological role of ROS produced by Nox enzymes in PAH is also well established. Thus, the expression of Nox1 was found to be increased in MCT rat model [89], while antioxidant therapy mediated decrease in Nox1 expression attenuated RV hypertrophy. Elevated Nox1 expression was shown to stimulate pulmonary artery smooth muscle cell proliferation and migration in rat PAH model [90,91].…”
Section: Sources Of Ros In Pah and The Role Of Gendermentioning
confidence: 99%